Internal fossil constraints have more effect on the age estimates of crown Palaeognathae than different phylogenomic data type - Selvatti, Alexandre Pedro; Takezaki, Naoko (Frontiers in Bioinformatics, 2025)
Palaeognathae is an ancient bird lineage that includes the volant tinamous and six flightless lineages: ostrich, rhea, cassowary, emu, kiwi (extant) and moa, elephant bird (extinct). Over the past decade, a consensus has emerged on the relationships within the group. In this consensus, the ostrich branch splits first, followed by rheas, a clade containing tinamou and moa and a clade with the emu and cassowary sister to the kiwi and elephant bird. However, the timing of the origin of these major clades remains uncertain. In phylogenomic studies, the origin of the crown Palaeognathae is typically dated to the K–Pg boundary (∼66 Ma), though one study suggested a younger Early Eocene age (∼51 Ma). This discrepancy might result from the number and position of fossil priors (calibration strategies) or by differences in genomic regions sampled (data types). We investigated the impact of calibration strategies and data types on the timing of the Palaeognathae root using genomic sequences from nuclear (noncoding [CNEE and UCE] and coding [first and second codon positions]) and mitogenomic datasets. The nuclear dataset included 14 Palaeognathae species (13 extant and the extinct moa), while the mitogenomic included 31 species, covering all extant and extinct lineages. The datasets were analyzed with and without internal calibrations. The age estimates were more influenced by calibration strategy than data type, although some nuclear data (CNEE) produced substantially younger ages except for the Casuariiformes node, whilst another dataset (PRM) from a previous study estimated younger ages for Casuariiformes compared to the other datasets. Nevertheless, our results consistently placed the origin of crown Palaeognathae around the K–Pg boundary (62–68 Ma), even when using the original dataset that produced the Eocene age. These findings demonstrate that multiple internal calibrations yield consistent results across different sequence types and taxon schemes, providing robust estimates of the crown Palaeognathae age. This improved timing enhances our understanding of the early evolutionary history of this clade, particularly regarding the placement of enigmatic Paleocene fossils, such as Lithornithidae and Diogenornis, which in this timeframe can be assigned to internal branches within the crown Palaeognathae.